2014
DOI: 10.1161/circgenetics.113.000259
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 , an Atrial Fibrillation Predisposition Gene, Directly Regulates Ion Transport and Intercalated Disc Genes

Abstract: Background Pitx2 is the homeobox gene located in proximity to the human 4q25 familial atrial fibrillation locus. When deleted in the mouse germline, Pitx2 haploinsufficiency predisposes to pacing induced atrial fibrillation indicating that reduced Pitx2 promotes an arrhythmogenic substrate. Previous work focused on Pitx2 developmental functions that predispose to atrial fibrillation. Although Pitx2 is expressed in postnatal left atrium, it is unknown whether Pitx2 has distinct postnatal and developmental funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 50 publications
8
104
1
Order By: Relevance
“…ChIP-Seq analysis using chromatin from adult mouse heart of the Pitx2 Flag allele (GEO accession no. GSE50401) (18) revealed that Pitx2 directly binds conserved chromatin upstream of miR-17-92 and miR-106b-25 (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ChIP-Seq analysis using chromatin from adult mouse heart of the Pitx2 Flag allele (GEO accession no. GSE50401) (18) revealed that Pitx2 directly binds conserved chromatin upstream of miR-17-92 and miR-106b-25 (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into miRs involved in AF pathogenesis, we performed miR expression profiling using hearts from Pitx2 null/null mutant and wild type, and ChIP-sequencing (ChIP-Seq) using hearts from the Pitx2-Flag allele (16,18), which express Pitx2 with a C-terminal Flag epitope tag ( Fig. 1 A and C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…63 In the postnatal atria, PTX2 also plays important role in the integrity of the intercalated discs, and knockout mice demonstrate evidence for SND. 64 Thus PTX2 has generated considerable interest as having a role in AF and possibly SND although evidence regarding the expression of PTX2 and its target genes in AF is still missing.…”
Section: Genetic Mutations Common To Snd and Afmentioning
confidence: 99%
“…[3][4][5] Reducing PITX2 levels alters the expression of several relevant left atrial genes, 6 and the effects of PITX2 on gene regulation are partially mediated by the miR-17 to miR-92 complex. 7 Preliminary analyses suggest that PITX2 regulates ion channel genes in the left atrium, 5,8 underpinning the observation that reduced atrial PITX2 levels shorten the atrial action potential and cause membrane potential depolarization. 3,9 On the basis of these insights and the impact of gene variants on chromosome 4q25 for AF, the genetic predisposition to AF has been identified as a promising candidate to develop personalized approaches to AF management.…”
Section: See Article By Gore-panter Et Almentioning
confidence: 99%